Carboxylate‐Driven Supramolecular Assemblies of Protonated meso‐Aryl‐Substituted Dipyrrolylpyrazoles. Issue 26 (26th May 2015) - Maeda, Hiromitsu; Chigusa, Kengo; Yamakado, Ryohei; Sakurai, Tsuneaki; Seki, Shu
Abstract Dipyrrolylpyrazole (dpp) derivatives possessing an aryl ring at the pyrazole 4‐position were synthesized. Upon protonation, modified dpp derivatives formed a variety of assembled structures through complexation with carboxylates, as observed by single‐crystal X‐ray and synchrotron XRD analyses. In particular, the complexation of protonated dpp species possessing long alkyl chains with dicarboxylates resulted in highly ordered assembled structures, the packing modes of which as lamellar structures were controlled by the lengths of the spacer units between two carboxylate moieties. The charge‐carrier transporting properties of the solid materials were also controlled by bound anions, including dicarboxylates.